The Ambulatory Teaching Minute: Development of Brief, Case-Based, Evidence-Based Medicine Exercises for the Internal Medicine Resident Continuity Clinic - Devin Oller (Association of American Medical Colleges, 2020)
Introduction There are limited data on best approaches for evidence-based medicine (EBM) teaching to residents in busy continuity clinic practices. Ambulatory Teaching Minute (ATM) exercises were designed to deliver brief, case-based, faculty-facilitated teaching to residents on high-yield ambulatory EBM topics. Methods I developed four ATM exercises, with each one-page handout containing a clinical case, a guided discussion of a research question and study design sparked by the case, a synopsis of a recent research article addressing this question, and a teaching guide for facilitation. Internal medicine residents received these ATM exercises over the course of their monthlong ambulatory block. Surveys that assessed resident engagement were obtained from faculty-facilitators (N = 4) and residents (N = 6) at the end of the ambulatory block. Results Residents were actively engaged in the exercise, with an average engagement score of 3.81 out of 5. Most respondents reported ATM exercises taking 6-10 minutes. The majority of respondents felt ATMs could be realistically completed once per week. Discussion In this preliminary assessment of a new tool for EBM teaching in clinic, positive engagement scores among preceptors and residents highlight the potential of ATMs to efficiently and effectively address EBM topics during limited teaching time in clinic.